2015
DOI: 10.1155/2015/635975
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lemon Balm (Melissa officinalisL.) Hydrogels: Quality and Bioactivity in Skin Cells

Abstract: The aim of the study was to design gels with lemon balm extract, assess their quality, and investigate the effect of rosmarinic acid on skin cells in normal conditions and under oxidative stress. Methods. The quantities of rosmarinic acid (RA) released from gels were evaluated by applying the HPLC technique. HaCaT cell viability was assessed by using the MTT method. ROS generation was measured using DCFH-DA dye. The results showed that the gelling material affected the release of RA content from gels. Lower an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The cytotoxicity of microfiber materials was evaluated to assess their biological compatibility. Cell viability was assessed by MTT method [20]. The cells were seeded onto 96-well plates at a density of 20,000 cells/well and incubated for 24 h. After incubation, cells were treated with different formulations: propolis containing electrospun microfibers and microfibers without propolis.…”
Section: Preparation Of Investigativementioning
confidence: 99%
“…The cytotoxicity of microfiber materials was evaluated to assess their biological compatibility. Cell viability was assessed by MTT method [20]. The cells were seeded onto 96-well plates at a density of 20,000 cells/well and incubated for 24 h. After incubation, cells were treated with different formulations: propolis containing electrospun microfibers and microfibers without propolis.…”
Section: Preparation Of Investigativementioning
confidence: 99%
“…Cell viability was assessed by the MTT method (11). The cells were seeded into 96-well plates at a density of 20,000 cells/well and incubated for 24 h. After incubation, cells were treated with different sample solutions: a) ME without added resveratrol (ME-control), b) ME-RES, and c) solution of resveratrol in DMSO (RES-control).…”
Section: Measurement Of Cell Viabilitymentioning
confidence: 99%
“…Psoriasis is a disease with in ammation origin [27]. A number of previous studies indicated anti-oxidant, anti-in ammatory, and immunomodulatory activities of Melissa o cinalis, damask rose, and fennel [24,28,29]. These herbs are a rich source of phenolic compounds such as avonoids, cumarin, tannin, caffeic acid, caffeic acid, and rosmarinic acid [30][31][32].…”
Section: Discussionmentioning
confidence: 99%